Prospective study of factors affecting medication adherence in diabetes mellitus patients - Agrawal, Navneet; Tiwari, Dharmendra (International Journal of Advances in Medicine, 2020)
Background: Treatment interruption is an obstacle in therapeutic control of diabetes mellitus. Treatment interruption leads to uncontrolled hyperglycemia which increases the risk of diabetes related complications. Aim of study the factors responsible for the treatment interruptions among the diabetes patients. Methods: Four hundred and ninety-one diabetes patients were studied at Diabetes, obesity and Thyroid center, Gwalior between September 2018 to December 2018. Responses were recorded using a detailed questionnaire consisting of 25 questions. Responses were recorded in terms of Yes or No along with the basic demographic details. Results: Male preponderance was reported (68.4%). Majority were off the diabetes treatment for last 1-5 months (78.8%). Most common response for the treatment interruption was long life medication period (73.7%) followed by the fact that majority were not aware of the consequences of missing the doses (68%), 66.6% due to the side effect of the medication and 57.8% had financial problem. Conclusions: Large number of diabetes patients had poor adherence. There are many modifiable factors which can be improved on individual basis to improve the glycemic outcomes.